Paparan Endotoksin Sebagai Faktor Risiko Penurunan Fungsi Paru Pada Pekerja Di Industri Tekstil Berbahan Baku Kapas: (Literatur Review) - Chamidatul Umaiyah; Retno Adriyani; Resawati Intan Savitri (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
Dust particles that enter the body through inhalation and into the lungs can cause disturbances in the respiratory tract. Dust particles produced from cotton fibers can contain endotoxin biological agents, inhalation of endotoxins can also cause other diseases namely, flu, bronchitis, chronic obstructive pulmonary and decreased lung function. This study was conducted for the analysis of endotoxin exposure in cotton dust as a risk factor for decreasing lung function of workers in the textile industry. The method used in writing this article is a literature review using ten scientific articles to analyze the level of endotoxins in cotton dust, the characteristics of workers and the decline in lung function in workers. The study found that the highest levels of endotoxins were found in cotton mills in Shanghai with annual endotoxin levels of 1,730-65,204 EU/m3. Endotoxins in cotton dust are found most abundantly in spinning and weaving units. Factors such as age, length of service and smoking status are risk factors for workers experiencing a decrease in lung function, while the influence of Personal Protective Equipment (PPE) still needs to be studied further.